Tobacco Control in State Comprehensive Cancer Control Plans: Opportunities for Decreasing Tobacco-Related Disease - Briseis A. Kilfoy, MPH; Karen Suchanek Hudmon, DrPH, MS; Jerold R. Mande, MPH (Centers for Disease Control and Prevention, 2007)
IntroductionComprehensive cancer control plans published by state, tribal, and territorial health agencies present an excellent opportunity to help prevent tobacco-related and other cancers. In this analysis, we sought to estimate the extent to which tobacco control activities outlined in state comprehensive cancer control plans incorporated the tobacco control recommendations presented by the Centers for Disease Control and Prevention (CDC) in Best Practices for Comprehensive Tobacco Control Programs - August 1999 (Best Practices) and The Guide to Community Preventive Services: Tobacco Use Prevention and Control (The Guide).MethodsWe analyzed the 39 available state comprehensive cancer control plans to determine which of the CDC tobacco control recommendations were incorporated. We then summarized these data across the 39 states.ResultsThe 39 states incorporated a mean of 5.6 recommendations from Best Practices (SD, 2.8; range, 0-9) and 3.9 recommendations from The Guide (SD, 1.9; range, 0-6). Nearly one-half of state plans (48.7%) addressed funding for tobacco control; of these, 52.6% (25.6% of total) delineated a specific, measurable goal for funding.ConclusionThe extent to which tobacco control is addressed in state comprehensive cancer control plans varies widely. Our analysis revealed opportunities for states to improve compliance with CDC's tobacco-related recommendations for cancer control.